Development and Design of ADPSS Co-simulation Technology for Large-Scale New Energy Electromagnetic Transient Simulation in High Performance Calculation. Issue 1 (1st December 2022) - Zheng, Weijie; Mu, Qing; Wang, Feng; Chen, Xujiang
Abstract: As large-scale wind and photovoltaic power generation incorporating into the AC power grid, the impact of new energy fluctuation and uncertainty on the transient stability of power grid have attracted widespread attention among researchers and engineers in the power industry. It is necessary to improve the transient simulation and modelling ability of new energy to provide a more efficient simulation platform for the stability research of new energy generation connecting to large power grid. In this paper, the ADPSS technology of large-scale new energy electromagnetic transient simulation is mainly studied in depth, including the following contents: the design and development of the interface and program of ADPSS-Matlab co-simulation, the improvement and optimization of the parallel high performance computing, and the verification of the accuracy of co-simulation for the modelling and experimental research with large-scale new energy simulation.